The impact of digital healthcare and teledentistry on dentistry in the 21st Century: a survey of Hungarian dentists - Orsolya Németh; Eszter Uhrin; Edmond Girasek; Julianna Boros; Zsuzsa Győrffy (BMC, 2023)
Abstract Background The era of digitalization has arrived in the field of dentistry. Teledentistry (TD), the use of digital solutions in dentistry, is already used in practice; however, only some possibilities are considered. During the COVID-19 pandemic, remote patient monitoring and patient communication had to be solved with TD, thus causing a rapid spread of new tools. In addition to digital workflows, patient communication, AI, and online forums are also available. Methods An online self-administered survey was developed for the study. The Hungarian Medical Chamber contacted potential respondents in a newsletter or e-mail. The Evasys survey system was used. The weighting procedure was executed for gender, age group, and type of settlement. A digital dental index variable was created and built with a linear regression model as a dependent variable. Explanatory variables are advantages, disadvantages, what would be necessary, experienced needs from the patients, and age. Results A total of 171 dentists completed the survey. The best-known digital technologies are online conferences (96.5%), E-prescriptions (94.6%), and digital impressions (86.0%). Unawareness is the highest in the field of artificial intelligence in dentistry (50.5%), store-forward solutions (43.5%), and real-time solutions (41.8%). The digital dental index is 14.24 (standard deviation (SD) = 5.5), with a high power of the model. Conclusion Hungarian dentists need to be made aware of all the possibilities of TD. In addition to digital workflows, store-forward and real-time solutions can be beneficial to substitute face-to-face visits. TD can be used effectively to monitor oral cavity changes and develop dental confidence and proper oral care habits. Our survey suggests that it is necessary and inevitable to integrate TD into both graduate and postgraduate education, which may form the basis of primary health care in the next decade.